Long term results of liver transplantation for alpha-1 antitrypsin deficiency. Issue 5 (May 2021) - Guillaud, Olivier; Jacquemin, Emmanuel; Couchonnal, Eduardo; Vanlemmens, Claire; Francoz, Claire; Chouik, Yasmina; Conti, Filomena; Duvoux, Christophe; Hilleret, Marie-Noëlle; Kamar, Nassim; Houssel-Debry, Pauline; Neau-Cransac, Martine; et al.
Abstract: Introduction: Liver transplantation (LT) is the therapeutic option for end-stage liver disease associated with alpha1 antitrypsin (A1AT) deficiency. The aim of the present retrospective study was to report on long-term outcomes following LT for A1AT deficiency. Methods: The medical records of 90 pediatric and adult patients transplanted between 1982 and 2017 in France and Geneva (Switzerland) were reviewed. Results: The study population consisted of 32 adults and 58 children; median age at transplant was 13.0 years (range: 0.2–65.1), and 65 were male (72.2%). Eighty-two patients (94.8% of children and 84.4% of adults) had the PI*ZZ genotype/phenotype and eight patients (8.9%) had the Pi*SZ genotype/phenotype. Eighty-four patients (93.3%) were transplanted for end-stage liver disease and six (all Pi*ZZ adults) for HCC. Median follow-up after LT was 13.6 years (0.1–31.7). The overall cumulative patient survival rates post-transplant were 97.8% at 1 year, and 95.5%, 95.5%, 92.0%, 89.1% at 5, 10, 15, 20 years respectively. The overall cumulative graft survival rates were 92.2% at 1 year, and 89.9%, 89.9%, 84.4%, 81.5% at 5, 10, 15 and 20 years, respectively. Conclusions: In a representative cohort of patients having presented with end-stage-liver disease or HCC secondary to A1AT, liver transplantation offered very good patient and graft survival rates.